2014
DOI: 10.1103/physrevb.89.075422
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced spin polarization in graphene due to Rashba spin-orbit interaction

Abstract: Spin polarization induced by an external electric field in graphene is considered theoretically in the linear response regime. The graphene is assumed to be deposited on a substrate which leads to the spin-orbit interaction of Rashba type. The induced spin polarization is shown to be in the graphene plane and perpendicular to the electric field. However, the spin polarization changes sign when the Fermi level, whose position can be controlled by an external gate voltage, crosses the Dirac points.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 28 publications
4
39
1
Order By: Relevance
“…For long relaxation times we get the same analytical formulas as those in the case of nonmagnetic graphene, 33 i.e.,…”
Section: Current-induced Spin Polarizationmentioning
confidence: 76%
See 1 more Smart Citation
“…For long relaxation times we get the same analytical formulas as those in the case of nonmagnetic graphene, 33 i.e.,…”
Section: Current-induced Spin Polarizationmentioning
confidence: 76%
“…Moreover, sign of the spinpolarization depends on the chemical potential and also on the sign of the Rashba spin-orbit coupling parameter. 33 When the Fermi level passes through the Dirac points, the spin polarization becomes reversed. In this paper we show that the current-induced spin polarization in magnetic graphene has generally all three components.…”
Section: Introductionmentioning
confidence: 99%
“…45 A nonzero spin polarization S y appears due to the imbalance of the distribution of electrons with k x > 0 and k x < 0. 41 …”
Section: A Spin Polarizationmentioning
confidence: 99%
“…Similarly, the spin polarization may be induced by the electric field as well. 41 In section 2 we describe the theoretical model. Numerical results on the thermally induced charge and heat currents are presented and discussed in section 3.…”
Section: Introductionmentioning
confidence: 99%
“…The extrinsic or Rashba SOC, however, results from the lack of inversion symmetry due to perpendicular electric fields, substrate effects, chemical doping, or curvature of graphene corrugations and can be responsible for inducing a spin polarization in graphene. [9,10] The influences of intrinsic and Rashba SOCs on the transport properties of graphene monolayer systems have extensively been studied in the recent years [5,6,[11][12][13][14]. For instance, it was shown that spin polarization induced by a charge current can reside in the graphene plane and perpendicular to the electric field while its sign changes by varying the Fermi level through an external gate voltage [11].…”
mentioning
confidence: 99%